History and Characteristics of the Arab Village Settlement Al-Munawar 13 Ulu, Palembang, South Sumatra - Akhmad Hamdi Asysyauki; Antonius Ardiyanto (Historia, 2026)
Palembang, with the beauty of the Musi River flowing through its city center, serves as a central point in the community's life. The city of Palembang is divided into two regions, namely Seberang Ulu (Ulu) and Seberang Ilir (Ilir), separated by the Musi River since the era of the Palembang Sultanate. The Arab ethnic community in Palembang is concentrated in several villages, one of which is Arabian Village Al-Munawar 13 Ulu Palembang, a settlement of the descendants of Habib Abdurrahman or Abdullah Al- Munawar who settled from Hadhramaut. They adhere strictly to the practice of marrying within the Arab lineage and reside along the banks of the Musi River. This village holds the potential for development but also requires preservation to prevent possible displacement in the future. The village's houses encompass various forms, including "limas" houses, warehouses, "Indies" houses, and raised platform houses. This research employs historical research methods to reveal the historical legacy, distinctive characteristics of Palembang, and the ethnic and cultural diversity in Arabian Village Al-Munawar 13 Ulu Palembang. The study concludes that Kampung Arab Al-Munawar 13 Ulu Palembang, existing for about 250 years, was the residence of traders' descendants from Hadhramaut. With marriage customs and settlement patterns reflecting the community's adaptation to its environment, this village holds significance in the historical and cultural diversity context of Palembang.